Library anxiety and fulfillment information needs of collage students of the Faculty of Mathematics and Natural Sciences Bengkulu University - Sinta Julianti; Nurhayati Darubekti; Lailatus Sa’diyah (D3 Perpustakaan Fakultas Vokasi Universitas Airlangga, 2022)
Background of the study: The development and knowledge, the library is used as a source to meet the information needs each student. However, ther are still many students who experience confusion in using the library so that library anxiety will occur and the fulfillment of their information needs will not be fulfilled. Purpose: This study aims to determine the level of library anxiety and the fulfilment of information needs for students of the faculty of Mathematics and Natural Sciences Bengkulu University batch 2019. Method: The method use is a descriptive quantitative research method. The sampling technique used is proportionate stratified random sampling, selected as many as 83 students Findings: the result showed that the level library anxiety in students of the Faculty of Mathematics and Natural Sciences Bengkulu University batch 2019 was 3,5 categorized with high level of anxiety. The level of fulfillment of information needs after being associated with library anxiety in students students of the Faculty of Mathematics and Natural Sciences Bengkulu University batch 2019 is 3,6 , categorized as a high level. Conclusion: The level of library anxiety that occurs in students of the Faculty of Mathematics and Natural Sciences Bengkulu University batch 2019 includes a high level of anxiety of fulfillment of their information needs after being associated with library anxiety is categorized with a high level so that the overal fulfillment of their information needs is not met